Indexing policy in University libraries: Diagnostic and analytical study with participatory research - Lopes Fujita, Mariangela Spotti [UNESP]; Piovezan dos Santos, Luciana Beatriz [UNESP] (Pontificia Universidade Catolica Campinas, 2016)
The purpose of indexing function is to represent content for the information retrieval. The success of this mediation depends on the indexing policy that takes into account the requirements, variables and the characteristic elements of organizational culture and the socio-cultural context of systems of information representation and retrieval. Considering that indexing in libraries is carried out during subject cataloguing, the different stages of requirements, variables and elements of the indexing policy of university libraries, which are identified in manuals or institutional documents on the systematic practice of indexing, need to be investigated. In order to identify university libraries that have an indexing policy and to verify how the cataloguers apply the indexing policy, we carried out a sampling diagnostic study at university libraries in the Southern and Southeast Brazilian regions and conducted an analytical study with participatory research of the sample selected. It was found that although indexing in most university libraries follows an indexing policy, it is not described in a manual. When investigating the requirements, variables and elements of the indexing policy, we identified the following: complete, partially complete and incomplete with flaws. Few libraries have a manual on indexing policy and the analysis during participatory research found that the indexing process is performed by the cataloguer without prior knowledge or application of an indexing policy which reflects the lack of continuing education and studies on indexing assessment through information retrieval in the catalogues.
Keywords: University libraries; Indexing; Indexing policy